THE EFFECT OF COOPERATIVE LEARNING MODELS ON SOUND TO IMPROVE ELEMENTARY SCHOOL STUDENTS' CRITICAL THINKING ABILITY - Eka Octavia; Sukma Dwi Anggraini; Lolitha Arum Permatasari; Susi Hermin Rusminati; Cholifah Tur Rosidah (Media Inovasi Pendidikan dan Publikasi, 2023)
This research was conducted to obtain an overview of the effect of the cooperative learning model on students' critical thinking skills in sound material. This research is motivated by the problem of teachers in the classroom who are still carrying out teaching and learning activities oriented towards material and students are not yet a center of learning so that students' ways of thinking cannot develop because the concepts possessed by students are only rote and temporary. The purpose of this activity is to add insight and help students to confirm their answers in practice questions, whether they are in accordance with the results of the experiment, so that science lessons are no longer focused on everything that must be memorized. This study uses a cooperative learning model. The subjects of this study consisted of learning model experts and fifth grade elementary school students. Data collection was carried out using the literature study method. The data analysis used is a qualitative description technique. The results of this research design are cooperative learning models that divide students into heterogeneous groups consisting of 4-5 individuals who work together in groups to solve a problem.